Coordination of school science classroom furnishings with anthropometric parameters for 11-12 year-old children - Rizman Herga, Nataša (Revija za elementarno izobraževanje, 2017)
The aim of the research was to explore the size suitability of school furnishings with the help of anthropometric measurements established on 11-12 year-old pupils. These pupils who have switched from single classroom teaching to teaching by subject and have lessons in specialized classrooms that are designed for a specific school subject. We were interested in the discrepancies between pupils' anthropometric dimensions and the size of school furniture in science classrooms. The study included 192 pupils (N=192) in the 6th and 7th grades of primary schools in North-Eastern Slovenia. Readings were made of the pupils' anthropometric dimensions, including stature, popliteal height, buttock-popliteal length, elbow height sitting, thigh thickness, subscapular height and hip width. Measurements of the school furniture showed that the dimensions of desks designed according to ISO 5970 correspond to a size 6 (for those between 173 and 184 cm tall). Results of the anthropometric measurements have shown that 6th grade pupils are on average 152 cm tall, 7th grade pupils 160 cm. The research thus indicated a serious mismatch between school furnishings and the anthropometric dimensions, an issue which can have serious consequences for pupils' development.
Keywords: interiors; šolske učilnice; interier; school furniture; anthropometry; šolsko pohištvo; antropometrija; science; primary schools; naravoslovje; osnovne šole